New TDOA algorithm based on Taylor series expansion in cellular networks - ZHANG Ling-wen; TAN Zhen-hui (Tongxin xuebao)
TDOA is the most potential positioning technique in cellular mobile telecommunication systems.Taylor series expansion method has been widely used in solving nonlinear equations for its high accuracy and good robustness.However,the performance of Taylor’s method depends highly on the initial estimation.Therefore one new algorithm（HOA,hybrid optimizing algorithm） was proposed which combines the Taylor series expansion method with steepest decent method.Steepest decent method is with the properties of fast convergence at the initial iterativeness and small computation complexity.HOA takes great advantages of both methods.Simulation results show that HOA has achieved better performance on positioning accuracy and efficiency.